Changes in the Proximate Composition, Fatty Acid and Mineral Contents of Catla catla of Loktak Lake by Different Cooking Methods - Dayami, Heikham; Sarojnalini, Chungkham (Asian Journal of Biological and Life Sciences)
Cooking methods are invariably found to influence the nutritional composition of protein and oilrich food such as fish. The effects of four different cooking methods (steaming, microwave cooking, frying and currying) were investigated on an important food fish, Catla catla, obtained from the Loktak lake, Manipur, India. The mean moisture, protein, fat and ash content of the raw fish were 79.69±0.06%, 15.50±0.03%, 1.45±0.20% and 1.26±0.11%, respectively. Significant changes were observed in the proximate composition, fatty acids and mineral content in the cooked samples. The moisture content was found to decrease in all the cooked fish compared to raw fish and the lowest moisture content was observed in fried fish samples. The protein and ash contents increased in all the cooked fish samples. Fat content was found to increase significantly in the fried fish sample compared to other fish samples. A significant reduction in n-3/n-6 and EPA + DHA/ C16 ratio was observed in the curried fish compared to others, whereas PUFA/SFA ratio increased in all cooked samples. An increase in the HH (hypocholesterolaemic/ hypercholesterolaemic fatty acid) ratio was observed in the fried and curried fish sample. Na content increased in the cooked sample whereas Ca, K, P, Fe and Cu were found to decrease. Zn content of steamed and curried samples did not differ compared to the raw sample and the microwave-cooked sample recorded highest value. The results of the study may be useful in selecting and designing proper cooking methods for the efficient utilization of nutrients in the fish Catla.
Keywords: Catla catla; Cooking methods; Fatty acids.; Proximate Composition; PUFA